Analysis of Ambiguity in Humor: A Pragmatic Analysis of Wordplay in YouTube Channel “We Got The Chocolates” - Moh. Kifly S. Rasyid; Hanisah Hanafi; Fahria Malabar (Transbahasa, 2026)
This study is grounded in the linguistic phenomenon of phonetic ambiguity as a strategy to create verbal humor in digital spoken discourse. The objective is to analyze how segmental sound structures are realised in phonetic wordplay and elucidate how these structures trigger dual meaning interpretations through a pragmatic framework. A descriptive qualitative research design was employed, using spoken dialogues from the